Limitations of Fat-Free Mass for the Assessment of Muscle Mass in Obesity - Jensen, Björn (Obes Facts, 2019)
BACKGROUND: A high amount of adipose tissue limits the accuracy of methods for body composition analysis in obesity. OBJECTIVES: The aim was to quantify and explain differences in fat-free mass (FFM) (as an index of skeletal muscle mass, SMM) measured with bioelectrical impedance analysis (BIA), dual energy X-ray absorptiometry (DXA), air displacement plethysmography (ADP), and deuterium dilution in comparison to multicompartment models, and to improve the results of BIA for obese subjects. METHODS: In 175 healthy subjects (87 men and 88 women, BMI 20–43.3 kg/m2, 18–65 years), FFM measured by these methods was compared with results from a 3- (3C) and a 4-compartment (4C) model. FFM4C was compared with SMM measured by magnetic resonance imaging. RESULTS: BIA and DXA overestimated and ADP underestimated FFM in comparison to 3C and 4C models with increasing BMI (all p < 0.001). Differences were largest for DXA. In obesity, BIA results were improved: valuecorrected = valueuncorrected – a(BMI – 30 kg/m2), a = 0.256 for FFM and a = 0.298 for SMM. SMM accounts for 45% of FFM in women and 49% in men. CONCLUSIONS: In obesity, the use of FFM is limited by a systematic error of reference methods. In addition, SMM accounts for about 50% of FFM only. Corrected measurement of SMM by BIA can overcome these drawbacks.